Transforming Hydroponics with IoT for Sustainable Water Management: Mengubah Hidroponik dengan IoT untuk Pengelolaan Air yang Berkelanjutan - Muchlason, Ahmad; Dhiya Ayuni, Shazana (Indonesian Journal of Law and Economics Review, 2024)
General Background: Urbanization is reducing agricultural land, necessitating innovative cultivation techniques like hydroponics to thrive in limited spaces. Specific Background: The study investigates the use of IoT technology in hydroponic systems, specifically focusing on remote monitoring and control of water pumps for efficient resource management. Knowledge Gap: Limited research has explored the use of IoT in optimizing water pump operations in hydroponic systems, focusing on energy management and remote accessibility. Aims: The research aims to create an IoT-based automated water pump control system for hydroponics, enabling remote monitoring and evaluating its energy efficiency and operational effectiveness. Results: The experimental setup, including an ESP32 microcontroller, ADS1115 module, solar charger controller, and submersible pump, demonstrated optimal performance with a time-based control strategy, achieving 96.7% current and 97% voltage accuracy. Novelty: The study showcases a successful model for integrating IoT in hydroponic systems, thereby enhancing sustainability and operational efficiency. Implications: The study underscores the potential of IoT technologies in enhancing water management in hydroponics, thereby providing a feasible solution to contemporary agricultural challenges in space-constrained environments. Highlights: IoT Integration: Remote control enhances hydroponic system monitoring and efficiency. Energy Optimization: Effective solar charging improves automated water pump performance. Real-time Monitoring: Enables accessible tracking from significant distances via smartphones. Keywords: Hydroponics, IoT, Water Management, ESP32, Energy Efficiency